Demographic effects of pesticides on biological control of Pacific spider mite (Tetranychus pacificus) by the western predatory mite (Galendromus occidentalis) - Stavrinides, Menelaos; Mills, Nicholas J. (My University, 2009)
The western predatory mite, Galendromus occidentalis (Nesbitt) (Acari: Phytoseiidae), is a predator of Pacific spider mite, Tetranychus pacificus McGregor (Acari: Tetranychidae), in California vineyards. We evaluated the effects of six pesticides on biological control of T. pacificus on grape plant microcosms in a two-way design: presence and absence of G. occidentalis crossed with presence and absence of pesticide. The insecticide imidacloprid did not affect T. pacificus population growth rate, but it led G. occidentalis populations close to extinction. As a result, T. pacificus populations grew significantly higher in microcosms with release of G. occidentalis and treated with imidacloprid than with G. occidentalis alone. The fungicide wettable sulfur significantly decreased T. pacificus population growth rate but it did not affect G. occidentalis. Consequently, T. pacificus populations were significantly lower in microcosms with release of G. occidentalis and treated with wettable sulfur than with G. occidentalis alone. The insecticide buprofezin had no effect on T. pacificus population growth rate. Although buprofezin did not impact the ability of G. occidentalis to suppress T. pacificus, it negatively affected G. occidentalis population growth rate. The fungicides trifloxystrobin and tebuconazole and the insecticide methoxyfenozide had no influence on T. pacificus or G. occidentalis population growth rates. Furthermore, none of the pesticides affected the sex ratio of G. occidentalis, but buprofezin, methoxyfenozide and trifloxystrobin affected its stage structure. Our study demonstrates that simultaneous testing of the demographic effects of pesticides on pests and natural enemies is essential for a full assessment of pesticide impacts on biological control. © 2008 Elsevier Inc. All rights reserved.
Keywords: Grapes; Instantaneous rate of increase; Microcosms; Pesticides; Predator; Vineyards